1977
DOI: 10.1136/gut.18.8.651
|View full text |Cite
|
Sign up to set email alerts
|

Internal sphincter and the nature of haemorrhoids.

Abstract: SUMMARY Internal anal sphincter activity has been studied in 84 patients with haemorrhoids and 40 asymptomatic subjects. Activity was estimated by measuring maximum resting anal pressure with a water filled anal balloon probe 7 mm in diameter connected to a strain gauge pressure transducer. There was greater activity of the internal sphincter in patients with haemorrhoids than in controls, but there was no significant relationship between sphincter activity and duration of symptoms, predominant symptom (bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
8

Year Published

1982
1982
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 3 publications
2
32
0
8
Order By: Relevance
“…It has also been reported that people with strain 19,20) , or those who spend a long time sitting on the toilet during bowel movements are likely to develop hemorrhoids 21) . Nevertheless, some hemorrhoid patients report normal bowel movements [22][23][24] ,; hence, there lacks sufficient evidence to make a correlation between chronic constipation and hemorrhoids.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that people with strain 19,20) , or those who spend a long time sitting on the toilet during bowel movements are likely to develop hemorrhoids 21) . Nevertheless, some hemorrhoid patients report normal bowel movements [22][23][24] ,; hence, there lacks sufficient evidence to make a correlation between chronic constipation and hemorrhoids.…”
Section: Discussionmentioning
confidence: 99%
“…Hipertonia do esfíncter anal interno também é descrita como uma possível causa de dor nas cirurgias anorretais, incluindo a hemorroidectomia. Desta forma, a esfincterotomia associada à hemorroidectomia tem sido proposta para reduzir este aumento da pressão anal, podendo, inclusive, diminuir as complicações pós-operatórias (dor, retenção urinária, estenose) 12,34,35 . Alguns autores consideram que hemorroidectomia isolada normaliza as pressões anais, uma vez que estas estariam aumentadas devido à presença dos coxins vasculares, e que a esfincterotomia, além de ser desnecessária, poderia causar incontinência anal 34,36 .…”
Section: Manometriaunclassified
“…Curiosamente, a intensidade da dor pós-operató-ria nos três primeiros dias (período da 1ª evacuação) foi maior nos pacientes do grupo com ELI, sugerindo que o espasmo do esfíncter anal não tem contribuição importante na dor pós-hemorroidectomia 34,39 . Neste estudo, assim como em outros 34 , observa-se que a associação de ELI no tratamento da doença hemorroidária não reduziu a dor pós-operatória.…”
Section: Manometriaunclassified
See 1 more Smart Citation
“…18 Smith et al has noted that urinary retention is the most common problem after haemorrhoidectomy, its degree related to the amount of surgery and the incisions required. 21 The anal sphincter has the same nerve root as the bladder sphincter.…”
mentioning
confidence: 99%